PENGARUH EKUITAS MEREK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO (SURVEI PADA MAHASISWA STIE SULTAN AGUNG SEMESTER VI TAHUN AKADEMIK 2016/2017) - Manurung, Ganda; Lie, Darwin; Butarbutar, Marisi; Inrawan, Ady (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The result of this research: 1. Brand equity, word of mouth and purchasing decisions already high. 2. The results of the regression analysis is Å¶ = 8,177 + 0,724X1 + 0,255X2, means this research have positive between of the brand equity and word of mouth on consumer purchasing decisions. 3. The results of correlation analysis obtained by r = 0,813 , it mean there is a high correlation and positive between the brand equity and word of mouth, to consumer purchasing. Purchasing decisions are influenced by the brand equity and word of mouth of 66.2%. 4. The hypothesis of research H0 is rejected and Ha is accepted, it means that the brand equity and word of mouth positive and significant effect of the purchase on the Oppo smartphone either simultaneously or partial. As for the suggestion of this research is to increase brand equity, the need for sophisticated feature innovations in accordance with the wishes of consumers selfie features with the quality front camera which is very nice as well as the resolution of the camera that is large enough for the sake of who were the selfie. To preserve the word of mouth on the Oppo smartphone, then spread information or promotion through advertising in prime time hours, preferably with a more interesting advertising concept that users increasingly Oppo smartphone products. Whereas, to maintain the increasing konsumenn purchasing decisions, by making innovations in presenting a unique design and specification put forward in order to get the attention of consumers. Keywords: Product Quality, Price, and Consumer Satisfaction.